Density of newly synthesized plasma membrane proteins in intracellular membranes. I. Stereological studies (The Rockefeller University Press, 1984)
As the spike proteins of Semliki Forest virus (SFV) pass from their site of synthesis in the endoplasmic reticulum (ER) to the cell surface, they must be concentrated and freed from endogenous proteins. To determine the magnitude of this sorting process we have measured the density of spike proteins in membranes of the intracellular transport pathway. In this first paper, using stereological procedures, we have estimated the surface areas of the ER, Golgi complex, and plasma membrane of infected and mock-infected baby hamster kidney cells. First, we estimated the mean cell volume in absolute units. This was done using a novel in situ method which is described in detail. Infection by SFV was found to have no effect on any of the parameters measured. In the accompanying paper ( Quinn , P., G. Griffiths, and G. Warren, 1984, J. Cell Biol., 2142-2147) these stereological estimates were combined with biochemical estimates of the amount of spike proteins in ER, Golgi complex, and plasma membrane to determine the density in the membranes of these compartments.